Polymorphisms in MAPK9 (rs4147385) and CSF1R (rs17725712) are associated with the development of inhibitors in patients with haemophilia A in North China. (31st May 2019) - Zhao, Mingming; Zhang, Yujing; Liu, Yanyan; Sun, Guoxun; Tian, Hong; Hong, Luojia
Abstract: Introduction: The formation of neutralizing antibodies (FVIII inhibitors) in haemophilia A patients is an immune response to the deficient factor. This process is multifactorial and includes environmental and genetic factors. Some genetic markers that play a decisive role in the immune response have been identified as risk factors for inhibitor development. Objective: Our aim was to investigate the association between polymorphisms in several genes involved in the regulation of the immune response and inhibitor development in patients with haemophilia A in North China. Methods: We analysed eight SNPs (MAPK9 rs4147385, CSF1R rs17725712, CD44 rs927335, STAT4 rs7574865, IKZF1 rs4917014, ETS1 rs6590330, BANK1 rs17266594 and rs10516487) by Snapshot SNP genotyping assays in 100 haemophilia A patients, including 29 with inhibitors and 71 without inhibitors. Results: Our results demonstrated that the rs17725712 A allele and the AA homozygous genotype of CSF1R were more frequent in patients with inhibitors. The rs4147385 G allele in MAPK9 was also more frequent in the inhibitor cohort. Conclusion: We confirmed an association of CSF1R rs17725712 and MAPK9 rs4147385 with inhibitor development in haemophilia A patients in North China.